A case of renal artery embolism treated by selective intra-arterial infusion of tissue plasminogen activator - Onur Baydar; Murat Başkurt; Uğur Coşkun; Murat Ersanlı (KARE Publishing, 2013)
Thromboembolic obstruction of the renal artery is a serious clinical problem, but rarely diagnosed. The diagnosis is not usually established until irreversible renal parenchymal damage occurs. Here, we present a case of renal artery thromboembolism in a patient who had atrial fibrillation and was treated by selective intra-arterial infusion of tissue plasminogen activator (TPA). A 69-year-old male was admitted to our hospital with a one-hour history of palpitation and epigastric pain. He had inferior myocardial infarction and percutaneous coronary intervention to the right coronary artery two weeks before. Coronary angiogram was performed, and no significant stenosis was detected. One hour later, epigastric pain spread to the left flank region. Spiral computerized tomography showed occlusion of the left renal artery. Emergency abdominal angiography was performed, and selective intra-arterial infusion of TPA was started promptly. The abdominal pain disappeared, and urine output remained adequate. Forty-eight hours later, angiographic follow-up confirmed the complete lysis of the thrombus in the left renal artery. No renal or hemorrhagic complications were observed, and the patient was discharged four days later with normalized renal function on oral anticoagulation.